Agora é com os pais!: Fecundidade na adolescência e juventude na perspectiva masculina em Belo Horizonte e Região Metropolitana - Carla Gomes Franco (2016)
The objective of this masters thesis is to understand the impacts of fertility occurred in adolescence and youth on the lives of men living in Belo Horizonte and in Metropolitan Region. Semi-structured interviews were conducted with twenty-two men between ages 21 and 30, who were parents for the first time in adolescence (between 15 and 19 years old) or in the youth (between 20 and 24 years old). The conversations made possible a retrospective approximation of the trajectories of these parents, from the moment of the beginning of the relationship with the mother of the child, through the news of the pregnancy and the reaction of the families, and arriving at the paternity itself, with regard of the care, involvement and current relationship with the child (ren). The results suggests that there was no difference between the parents who had children as teenagers or those who had as young man as the reaction to the news of pregnancy - most speak of "shock" and "fright". When asked how they would receive the same news these days, some fathers said that if they were having a planned child, the reaction would be "calmer" and less shocking than in the past. Regarding as the decision to live together after the news of the pregnancy, there was no difference between the parents who had their children in their adolescence or in their youth. However, more young parents than adolescent parents remain with the mothers of their children. When asked about their desire to have more children, only three respondents answers they did not want more children - one has 3 children, one has 2 children and one has 1 child. Thus, of the twenty-two interviewees, only one intends to have only one child, therefore, at least in this small and selective group, the fecundity approaches the level of replacement. When they speak of the future fertility of their sons and daughters, they emphasize the "right time" and the phases that must be fulfilled before having a child - study, work and marriage. Finally, the meaning of being a father is strongly associated with the term "responsibility," which also appears in speeches as a feature of adult life. Additionally to being responsible, being a father is linked to be present, educate and give love and affection, which indicates changes in the perception of the father figure in relation to the past, but without leaving aside the traditional role of the father provider, who "sustains the house and the son".